Off-clamp robot-assisted partial nephrectomy for purely hilar tumors: Technique, perioperative, oncologic and functional outcomes from a single center series. Issue 8 (August 2022) - Ferriero, Mariaconsiglia; Brassetti, Aldo; Mastroianni, Riccardo; Costantini, Manuela; Tuderti, Gabriele; Anceschi, Umberto; Bove, Alfredo Maria; Misuraca, Leonardo; Guaglianone, Salvatore; Gallucci, Michele; Simone, Giuseppe
Abstract: Objectives: Purely hilar lesions and those abutting the main renal artery or vein may be significantly different in terms of surgical complexity, requiring different resection strategies. To describe surgical technique and to assess its safety, oncologic and functional outcomes of a single centre experience of Off-Clamp Robotic Partial Nephrectomy (Off-C RPN) for purely hilar renal masses. Methods: The Institutional Review Board renal cancer database was queried for: "robotic", "partial nephrectomy" and "hilar". Baseline imaging was reviewed for all cases to strictly select patients with purely hilar tumors, defined as tumors arising into the renal hilum without any exophytic growth. Off-C RPN with straight access to the hilum was performed in all cases. We reported baseline, perioperative, oncologic and functional outcomes of the institutional series of purely hilar masses treated with Off-C RPN. Results: Between 2011 and 2019, 680 Off-C RPN were performed. Overall, 20 cases were classified as "hilar" renal tumors. Ten lesions abutting the main renal artery or vein were excluded leaving 10 purely hilar cases for analysis. Median operative time was 85 (range 68–115) minutes. No high-grade complications occurred. One patient (10%) required blood transfusion. At a median follow-up of 27 months, one renal recurrence and one newly onset Chronic Kidney Disease stage 3A was observed. Conclusions: RPN for purely hilar tumors has been poorly addressed and distinguishing purely hilar from tumors abutting the hilar vessels may have significant technical implications. In tertiary referral centers, Off-C RPN for purely hilar tumors provides excellent perioperative, oncologic and functional outcomes. Highlights: Hilar renal tumors are challenging cases, requiring different resection strategies. Purely hilar masses best suited off-clamp robotic partial nephrectomy. It is a feasible and safe approach, providing excellent outcomes. The technique remains demanding and should be referred to high volume centres.